Infectious Complications With Nondaily Versus Daily Infusion of Intravenous Fat Emulsions in Non–Critically Ill Adults. (5th November 2013) - Chheng, Mary Lou; Heidbreder, Charles; Btaiche, Imad F.; Blackmer, Allison Beck
Abstract : Background : Increased risk for infection has been associated with the administration of intravenous fat emulsion (IVFE). Typically, IVFE is infused daily as part of the parenteral nutrition (PN) regimen. However, a national IVFE shortage in 2010 compelled institutions to restrict administration to nondaily. This retrospective study evaluated the rate of infections associated with the nondaily as compared to daily IVFE infusion in hospitalized adult patients. Methods : Patients in the study group received nondaily IVFE during the shortage period, and patients in the control group received daily IVFE. The primary outcomes were the development of catheter‐related bloodstream infections (CR‐BSIs) or any bloodstream infection (BSI). Secondary outcomes were the development of respiratory, urinary, wound, or other infections. Results : Included in the study were 52 patients, 33 patients in the study group and 19 patients in the control group. There were no CR‐BSIs reported. BSIs occurred in 1 patient in the study group. The total number of infections and urinary tract infections (UTIs) per 1000 catheter days were not different between the 2 groups (45.28 vs 21.24, P = .203) and (24.39 vs 5.525, P = .099), respectively. Survival analyses showed no difference between the 2 groups for the time to first infection (11.24 vs 6.59 days, P = .30) and time to first UTI (11.97 vs 7 days, P = .093), respectively. Conclusions : Nondaily vs daily IVFE infusion did not have a significant effect on the risk of infection or time to development of infection; however, results are limited due to the small sample size. Large prospective randomized clinical trials are needed to further evaluate the effect of daily as compared to nondaily IVFE infusion on infectious complications.